Microwave driven synthesis of narrow bandgap alpha-tin nanoparticles on silicon. (May 2022) - Mazzetta, I.; Viti, L.; Rigoni, F.; Quaranta, S.; Gasparotto, A.; Barucca, G.; Palma, F.; Riello, P.; Cattaruzza, E.; Asgari, M.; Vitiello, M.; Irrera, F.
Graphical abstract: Highlights: A CMOS-compatible MW-driven process resulting into α-Sn over Si was proposed. A 52 meV direct bandgap was extrapolated from FTIR measurements. An α-Sn phase stable up to 200 °C was synthesized. MW-enhanced atomic diffusion and fast cooling may favor formation of α-Sn domains. α-Sn domains/amorphous oxide core/shell structure was found. Abstract: This work proposes a microwave-based synthetic route for the preparation of tin nanospheres with a diamond-like α-phase structure on silicon. The main characteristics of the synthesized material are an extraordinarily narrow (around 50 meV) direct bandgap and an improved thermal stability (up to 200° C). Structural and compositional characterizations showed a core–shell structure comprised of an outer amorphous oxide shell and inner core containing α-phase tin domains. Microwaves turned out to be instrumental in achieving the specific nanostructures reported, due to their peculiar heating characteristics. Low pressure, low temperature and compatibility with integrated circuits manufacturing represent the most innovative features of the present synthetic process.